Prioritizing the Entrepreneurial Exit Causes at Business Growth Stages - Mohammadreza Parsanejad; Seyyed Rashid Shahcheragh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The entrepreneur's exit is an important decision during the entrepreneurial process. The exit is part of the entrepreneurial process and significantly impacts the business ecosystem and the economy. The study of the entrepreneurial process is incomplete without examining the exit phenomenon. In this research, we intend to achieve a more accurate understanding of this phenomenon by analyzing the entrepreneurial exit during the six stages of growth. Prioritizing the reasons for exit for the business and social entrepreneur will contribute to a more accurate understanding of this area. Methodology: The research sample consisted of experts and entrepreneurs gathered through snowball sampling. We used repeated-measures methods to rank the reasons for exit reasons. Findings: After reviewing the opinions of experts and entrepreneurs, it was found that the importance of exit reasons in both types of business and social entrepreneurs changes during the different stages of business growth. On the other hand, the reasons for exit from the entrepreneur's viewpoint are not necessarily related, so the importance of exit causes from the perspective of the individual and social entrepreneur is different. Still, they are identical from the perspective of business and social enterprise. Originality/Value: This study uses the method of measuring duplicate measures to rank the reasons for the departure of Iranian entrepreneurs (at the commercial and social level) during different stages of business growth. The study indicates that the exit causes differ in various stages and cannot be included in the list for all businesses regardless of their growth stage.